Synthesis and characterization of sprayed CIGS thin films for photovoltaic application. (2020) - Kotbi, A.; Hartiti, B.; Fadili, S.; Labrim, H.; Ridah, A.; Thevenin, P.
Abstract: CuInGaS2 (CIGS) absorber materials were synthesis by spray pyrolysis on glass substrates, using special concentrations of gallium in the sputtering solutions ([Ga 3+ ] = y .[In 3+ ], y vary from 5 to 25 at.% by a step of 10 at.%). CIGS thin films were investigated by X-ray diffraction, Raman spectroscopy, UV–Vis spectroscopy and four point probing technique. The structural analyses confirm that all CIGS thin films have a chalcopyrite structures. Optical studies reveal that the optical band gap energy of the films increases by increasing the proportion of gallium and is in the range of 1.50–1.56 eV. The electrical properties present an increase in sheet resistivity with the proportion of gallium in the solution.